Clinical Characteristic and Outcome of Acute Lower Respiratory Tract Infection in Children with Congenital Heart Disease - Krystle Gabriela; Rahmat Budi Kuswiyanto; Fenny Dwiyatnaningrum (Althea Medical Journal, 2015)
Background: Acute Lower Respiratory Tract Infection (ALRTI) is the leading cause of deaths in children under 5 years of age worldwide, and has high morbidity and mortality in children with Congenital Heart Disease (CHD). The objective of this study was to obtain the incidence, clinical characteristic, and outcome of ALRTI children with CHD.Methods: A retrospective hospital-based study was conducted from January 2007–December 2011 to medical record of child patients with ALRTI and CHD in the Department of Child Health of Dr. Hasan Sadikin General Hospital, Bandung. The diagnosis of CHD was determined by echocardiography. The collected data was analyzed and presented in percentage shown in tables.Results : From 3,897 children who had ALRTI, there were 149 children with CHD (3.8%), with 11.4% of whom founded with recurrent episodes. This happened often in girls than boys with quite similar ratio of 1.37: 1.The majority of children (80%) was under 1 year old of age, 72.5% with malnutrition, and 24.8% with severe malnutrition. Clinical symptoms mostly found were difficulty of breathing (98%), fever (85.2%), cough (75.2%), and runny nose (63.1%). The most common types of CHD were Patent Ductus Arteriosus (47.6%), followed by Ventricular Septal Defect (47%). Bronchopneumonia (86.6%) was the common type of ALRTI. The length of stay was mostly less than 10 days (70.5%). From all the children 43.7% had complications, and 6.7% died.Conclusions: The ALRTI in children with CHD is not common and has good outcome. The majority for CHD lesions are Patent Ductus Arteriosus and Ventricular Septal Defect while for ALRTI is Bronchopneumonia. DOI: 10.15850/amj.v2n3.483